Facile Material Design Concept for Co-Free Lithium Excess Nickel-Manganese Oxide as High-Capacity Positive Electrode Material. Issue 11 (16th November 2021) - Tabuchi, Mitsuharu; Kitta, Mitsunori; Yazawa, Koji; Kubota, Kei
Abstract : High-capacity Li1+x (Ni0.3 Mn0.7 )1-x O2, (0 < x < 1/3) samples were synthesized by the coprecipitation–calcination method. Both electrochemical cycle and high-rate performances were drastically improved by selecting an N2 atmosphere as final calcination. Scanning transmission electron microscopy—energy dispersive X-ray spectroscopy analysis showed that the sample calcined in an N2 atmosphere had a more homogeneous transition metal distribution into primary particles than that calcined in air. The solid-state 7 Li nuclear magnetic resonance data showed that electrochemically inactive domains were only diminished for the sample calcined in an N2 atmosphere after electrochemical activation. X-ray Rietveld analysis revealed that the suitable transition metal distribution and content of the samples were different from those of typical layered rock-salt materials. Only that calcined in an N2 atmosphere had no spinel formation during charging and no oxide ion insertion reaction during discharging. No positive Co substitution effect was observed under the optimized preparation conditions. At the 100th cycle, the discharge capacity was 216 mAh g −1, which corresponds to 87% of the initial capacity (251 mAh g −1 ) at optimizing synthetic condition.